EFFECTIVE WAYS OF TEACHING ENGLISH (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Currently, there are many methods for studying a foreign language in educational institutions. Each of the methods has certain features, some are more popular and in demand, some are less. This article will consider effective ways of teaching English.